Students’ usage behavior toward digital exam pads in Indian university settings - Shandilya, Abhinav Kumar; Kumar, Dilip (Institute of Advanced Engineering and Science, 2025)
This study investigates the factors influencing undergraduate students’ acceptance and usage of digital exam pads in the context of Indian higher education by utilizing the variables of the unified theory of acceptance and use of technology (UTAUT) and its extended version, UTAUT2. The shift towards paperless examinations is vital for sustainability and efficiency in education, yet understanding the determinants of student adoption remains a challenge. To address this, the study collected data from 480 undergraduate students from Jharkhand and Karnataka, India, and the proposed model was tested using partial least squares structural equation modeling (PLS-SEM). The results revealed that performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), and hedonic motivations (HM) significantly influence students’ behavioral intentions to use digital exam pads, which in turn positively affect actual usage behavior (UB). Additionally, gender was found to moderate the relationship between HM and BI. The study concludes that the UTAUT model effectively explains digital exam pad adoption, offering practical insights for universities aiming to implement such technologies. The findings underscore the need for targeted strategies to enhance student engagement with digital tools, particularly considering gender differences.